Counterexample for the 2-approximation of finding partitions of rectilinear polygons with minimum stabbing number - Piva, Breno (2016)
This paper presents a counterexample for the approximation algorithm proposed by Durocher and Mehrabi [1] for the general problem of finding a rectangular partition of a rectilinear polygon with minimum stabbing number.